2019
DOI: 10.1021/acsami.9b17777
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Enzymes on Graphene as Nanobiocatalyst

Abstract: Using enzymes as bioelectrocatalysts is an important step toward the next level of biotechnology for energy production. In such biocatalysts, a sacrificial cofactor as an electron and proton source is needed. This is a great obstacle for upscaling, due to cofactor instability and product separation issues, which increase the costs. Here, we report a cofactor-free electroreduction of CO2 to a high energy density chemical (methanol) catalyzed by enzyme–graphene hybrids. The biocatalyst consists of dehydrogenases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 88 publications
0
44
0
Order By: Relevance
“…Graphene acid is a conductive graphene derivative with a well-defined chemistry, as both sides of graphene are densely (with ~15% degree of functionalization) and homogenously decorated by carboxyl groups ( Bakandritsos et al, 2017 ). The carboxyl groups of graphene acid enable efficient covalent enzyme immobilization ( Seelajaroen et al, 2020 ), which can be exploited in electrochemical sensing in the future.…”
Section: Graphene-based Materials In Virus Sensingmentioning
confidence: 99%
“…Graphene acid is a conductive graphene derivative with a well-defined chemistry, as both sides of graphene are densely (with ~15% degree of functionalization) and homogenously decorated by carboxyl groups ( Bakandritsos et al, 2017 ). The carboxyl groups of graphene acid enable efficient covalent enzyme immobilization ( Seelajaroen et al, 2020 ), which can be exploited in electrochemical sensing in the future.…”
Section: Graphene-based Materials In Virus Sensingmentioning
confidence: 99%
“…[ 172 ] In comparison to noble metals, carbon nanomaterials display the advantages for biosensing due to following three aspects: 1) the carbon nanomaterials are more cost‐effective than noble metals (carbon of ≈$ 0.03 per gram, Au of ≈$60 per gram/Ag of ≈$25 per gram/Pt of ≈$34 per gram); [ 173,174 ] 2) the carbon nanomaterials are obtained from plentiful raw materials especially sustainable biomass materials, superior to the noble metals with limited source; 3) the carbon nanomaterials are prepared with uniformity and structural diversity, while preparing noble metals with controllable composition and structures have been still limited. [ 175–177 ] Specifically, the classical carbon materials own high thermal/electrical conductivity and immense derivatization capability, [ 178,179 ] thus supporting molecule (e.g., peptide [ 180 ] ) and cell detection. [ 181,182 ] The carbon hybrid materials, that carbon materials are doped with other elements, display good biocompatibility, abundant catalytic sites and high thermal/chemical stability for diagnostic and therapeutic applications.…”
Section: The Application Of Sustainable Carbon Materials In Catalysismentioning
confidence: 99%
“…Ve r y r e c e n t l y H a t h a i c h a n o k Seelajeroen et al demonstrated the immobilization of three different enzymes on a functionalized graphene. 16 In these nano-bio-catalysts we used graphene as electrical platform to hook three different enzymes thereon and perform the biocatalysis from CO 2 over formate over formaldehyde all the way to methanol (see Fig. 13).…”
Section: Immobilized Enzyme-functionalized Electrodesmentioning
confidence: 99%
“…Reproduced with permission from reference 15 . Figure 13: Schematic description of electrically addressing three different enzymes immobilized on a functionalized graphene sheet as described in reference 16 .…”
mentioning
confidence: 99%